Ensino da escrita em turmas multisseriadas: uma análise das atividades desenvolvidas no ensino fundamental anos iniciais durante a pandemia do Covid – 19 - Guimarães, Jeniffer Camila da Silva (2022)
The research presented here aimed to investigate how the process of teaching writing in a multigrade class occurred in times of a pandemic. This study is located in the field of studies of the line of research Teaching and Learning Processes, presents a qualitative approach and is characterized as exploratory research. In this sense, data collection was carried out through semi-structured interviews and documental analysis of the writing activities carried out by students enrolled in elementary school in the early years in a multigrade class. For content analysis, the approach of Bardin (1997 and 2016), Ludke and André (1986) and Bogdan and Biklen (1994) and Minayo (1994) was used. The results obtained revealed that the teaching process of writing is directly related to the teaching conception of the teacher responsible for the class and to the students' learning needs. Through the research findings, it appears that there is no teaching recipe that should be applied by all teachers, but a particular teaching strategy for each school context.